2021
DOI: 10.1155/2021/5669412
|View full text |Cite
|
Sign up to set email alerts
|

Iron Metabolism and Idiopathic Pulmonary Arterial Hypertension: New Insights from Bioinformatic Analysis

Abstract: Idiopathic pulmonary arterial hypertension (IPAH) is a rare vascular disease with a poor prognosis, and the mechanism of its development remains unclear. Further molecular pathology studies may contribute to a comprehensive understanding of IPAH and provide new insights into diagnostic markers and potential therapeutic targets. Iron deficiency has been reported in 43-63% of patients with IPAH and is associated with reduced exercise capacity and higher mortality, suggesting that dysregulated iron metabolism may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…Levels of hepcidin have been shown to be higher in idiopathic PAH than in healthy controls, which might be explained by various factors including BMPR2 (bone morphogenetic protein receptor type 2) mutation/downstream pathway dysfunction and enhanced inflammatory response. 104,110 At the same time, the intracellular iron overload which parallels the circulating ID leads to mitochondrial dysfunction and increases oxidative stress, which in turn contributes to the progression of PH by inducing pulmonary vascular remodelling. 110,111 In the Jackson Heart Study enrolling 2800 individuals, ID was not associated with PH, and there was no association between ferritin or serum iron concentration and PH.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…Levels of hepcidin have been shown to be higher in idiopathic PAH than in healthy controls, which might be explained by various factors including BMPR2 (bone morphogenetic protein receptor type 2) mutation/downstream pathway dysfunction and enhanced inflammatory response. 104,110 At the same time, the intracellular iron overload which parallels the circulating ID leads to mitochondrial dysfunction and increases oxidative stress, which in turn contributes to the progression of PH by inducing pulmonary vascular remodelling. 110,111 In the Jackson Heart Study enrolling 2800 individuals, ID was not associated with PH, and there was no association between ferritin or serum iron concentration and PH.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…Recently, interest in trace elements has elevated since their abilities to induce a multitude of microcosmic events affecting cell fate, particularly ferroptosis, an iron-dependent mediated form of cell death [ 151 ]. Bioinformatic data predicted that CA probably alleviated intracellular iron shortage to inhibit pulmonary vascular remodeling and reduce pulmonary artery pressure, then postponing the deterioration of PAH [ 159 ]. As the contribution of ferroptosis regulation to the pharmacological benefits of CA is largely unknown, detailed basic researches are rewarding to be employed for determining whether CA diminishes vascular injury by improving the activation of ferroptosis.…”
Section: Other Recent Advances In the Mechanisms Of Ca Against Cvdsmentioning
confidence: 99%
“… Li et al (2020 ) conducted a comprehensive miRNA–mRNA network analysis and identified that AQP9 was one of the five hub genes possibly involved in the pathogenesis of idiopathic PAH. TXNRD1 was also decreased and identified as an iron metabolism-associated hub gene in lungs of idiopathic PAH ( Zou et al, 2021 ). S100A8 , a ligand of receptor for advanced glycation end products, was overexpressed in PAH patient-derived pulmonary artery smooth muscle cells compared to those from non-PAH control subjects in the absence of any external growth stimulus ( Nakamura et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%